Study of Changes in Mangrove Areas Around the Barombong Maritime Polytechnic - Irwan Jaya; Faisal Saransi; Heri Sutanto; Suryansyah Surahman (Politeknik Pelayaran Barombong, 2024)
Recently, coastlines in several areas of Indonesia have experienced erosion, which is quite worrying. Makassar City is one of 30 coastal cities in Indonesia that is estimated to be potentially affected by rising sea levels. As is the case in the Tanjung Bunga and Barombong Beach areas, the level of abrasion is very high. The beaches in these two areas have experienced a decline in coastline over the years, so they have moved far inland. This is caused by several factors, such as the influence of waves that occur in coastal waters, the influence of local winds, the presence of tides and the existence of coastal currents around Tanjung Bunga due to the lack of physical wave dampening structures, such as the lack of artificial structures/ buildings and mangrove forests. as physical protection of the coast. This study was conducted to identify changes in the extent of mangrove cover around the Barombong Shipping Polytechnic campus concerning data and information processing using a geographic information system (GIS). Based on the results of the data analysis, there has been a change in the extent of the mangrove ecosystem around the study location. This change in area can be seen from the upward trend over the last ten years. In 2013-2018, there was an increase of ​​30.38% or around 8.2 ha. In 2018-2023, there was an increase in the area of ​​7.36% or around 2.6 ha; in 2013-2023, there was an increase of ​​39.97% or around 10.8 ha.